2018
DOI: 10.21037/jtd.2018.06.150
|View full text |Cite
|
Sign up to set email alerts
|

Non-transfemoral access sites for transcatheter aortic valve replacement

Abstract: Transfemoral access is currently the standard and preferred access site for transcatheter aortic valve replacement (TAVR), though novel approaches are emerging to expand treatment options for the increasing numbers of patients with a contraindication for the traditional route. Previous publications have provided comparisons between two TAVR access sites, primarily transfemoral versus one of the novel approaches, while others have compared three or four novel approaches. The aim of this report is to provide a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 76 publications
2
28
1
1
Order By: Relevance
“…The second most common complication was renal failure, with a 8.2% rate, which was probably associated with surgical trauma and the systemic inflammatory response, as a possible cause of injury [14,21]. These results were similar to those previously described [18,22,23].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The second most common complication was renal failure, with a 8.2% rate, which was probably associated with surgical trauma and the systemic inflammatory response, as a possible cause of injury [14,21]. These results were similar to those previously described [18,22,23].…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, in a study by Walter et al, the authors observed lower 30-day mortality with a survival rate of 91%, but with a similar death rate of 27% at 12 months of follow-up. In summary, currently available data showed relatively lower 30-day mortality rate at 12.2 % and only 3.8% in the PARTNER TA group; 12-month mortality was 32.2% and 29.0%, respectively [5,14]. The 12-month all-cause mortality reached 24.6% but in the present study TA was the only possible method of invasive treatment in the group of patients with many comorbidities.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…19 Although left axillary artery access has favorable anatomical configuration and allows more coaxial orientation of the valve with the aortic root, thereby to the greatest degree in perpendicular to the aortic annulus, the right axillary artery is inheritably associated with major vascular tortuosity and challenging implantation angulations. 3,12,20 Therefore, this approach has yet to be widely accepted.…”
Section: Commentmentioning
confidence: 99%
“…Because a considerable percentage of patients undergoing TAVR evaluation have peripheral vascular disease that precludes transfemoral approach TAVR, other access routes have been used as alternatives. 2,3 Among the alternative access routes that have been explored, transaxillary (TAx)-TAVR has been shown to have equivalent outcomes to transfemoral approach. [4][5][6] Compared with transaortic or transapical access routes, TAx-TAVR is less invasive and was associated with improved recovery time in studies with the CoreValve (Medtronic, Minneapolis, MN).…”
mentioning
confidence: 99%